Navigating Cultural Diversity: The Lived Experiences of Timor Leste Students - Budury, Syiddatul; Azizah, Nurul Latifatul; Afridah, Wiwik (KnE Social Sciences, 2025)
Strong adaptability skills and a supportive learning environment are essential for international students, particularly if they are attending a university with a strong religious affiliation and come from diverse cultural, religious, and moral backgrounds The aim of this study was to have a better understanding of the significant experiences that Timor Leste students had while attending a private university in Surabaya, Indonesia. In this phenomenological study, sampling was purposive and was based on information shared by two Timor Leste students. The data were collected through interviews, and the analysis was thematic. Five key elements were identified: recognition of diversity, social justice, tolerance, equality, and social integration. These components are required to promote interaction between students with different backgrounds. In terms of interaction within diversity, they felt they received the same treatment as local students. The findings revealed that they sometimes struggle with language when conversing with their peers, who occasionally use Javanese. According to the study’s findings, more assistance should be provided to Timor Leste students residing in Surabaya, Indonesia, who are having communication difficulties.